Improving the repeatability of dynamic olfactometry according to EN 13725: A case study for pig odour. (September 2017) - Hove, Nathalie C.Y.; Demeyer, Peter; Van der Heyden, Caroline; Van Weyenberg, Stephanie; Van Langenhove, Herman
Abstract : Dynamic olfactometry, according to the standard EN 13725:2003 (CEN, 2003), is the reference method in Europe to measure odour concentrations and emissions from agricultural and industrial facilities. Laboratory measures to improve the precision (repeatability) of olfactometry were investigated here, focussing on the reference odorant, n-butanol and on pig house odour as an environmental odour. The effects of panel size, of the panellists' performance level, of the odour type and of the number of rounds on the olfactometric precision were studied. A precision-analysis tool was developed in Matlab, which randomly constituted 20, 250 odour panels and randomly selected odour thresholds to generate 40, 500 odour concentrations, calculated according to EN 13725. These simulations were performed, using 10 datasets of in total 776 olfactometric thresholds, measured by CEN-qualified panellists. The first results (reference odorant only) indicated that the panellists' performance level, the panel size and the number of rounds all significantly affected the laboratory's repeatability and that increasing the panel size, improved the repeatability the most. In a second study, comparing n-butanol and pig odour, as well odour type, as panel size, as the number of rounds significantly influenced the laboratory's repeatability. Odour type had the highest influence, followed by an increasing panel size. Based on these two studies, increasing the panel size seems a good means for improving the repeatability. For pig odour specifically, increasing the number of rounds from 2 to 3, improved the repeatability as much as one extra panellist. Highlights: Investigating laboratory measures to improve the precision of dynamic olfactometry. Extensive simulation of the precision of olfactometry for n-butanol and pig odour. Significant effects of the panel size and of the number of dilutions' rounds. Significant effects of the odour type and of the panellists' performance level. Precision for pig odour was significantly higher than that for reference n-butanol.